Analysis of the canonical initiation and trans-acting factor requirements of 5'TOP containing mRNAs - Garside, Paul (2010)
All eukaryotic mRNAs process a cap structure (m7G(5')ppp(5')N) at the S' end of their message and most have an A as the first nucleotide after the cap. However, 30% of messages within eukaryotic cells have a C (m7G(t')ppp(5')C) as the first nucleotide followed by a short polypyrimidine tract. These mRNAs are termed TOP (Tenninal Oligopyrimidine tract) messages and are co-ordinately regulated by mitogenic, growth and nutritional stimuli. This work describes the construction of a reporter vector that encodes mRNA containing the TOP motif, and its use in a series of systematic experiments to further investigate the translational regulation of TOP messages. Given that TOP containing mRNAs are known to encode proteins involved in the translational machinery, these findings have important implications with regard to translational control and translation related disease. In this study, reporter vectors have been used to investigate the role of the mTOR and PI3K signalling pathways, which have previously been implicated in the translational regulation of TOP containing mRNAs. The data obtained suggests that the mTOR signalling pathway may be involved in the regulation of TOP containing mRNAs. The canonical initiation and frans-acting factor requirements of TOP mRNAs were also investigated using a combination of protein over-expression and affinity purification of TOP-containing-mRNA:protein complexes. The data obtained raises the possibility that eIF4E may not be required in the initiation of TOP containing mRNA translation. The candidate trans-acting factors that were identified include La, ILF2 and EBPl, the latter of which has previously been shown to associate with mature ribosomes in the cytoplasm. Finally, affinity purification of TOP-containing-mRNA:microRNA complexes was carried out. Candidate microRNAs which may be involved in the regulation of TOP containing mRNAs were identified. The data obtained was consistent with a previous study, which suggested that microRNA-IOa may bind to the S'UTR of TOP containing mRNAs